An in-depth interview method to explore the retrospective experiences of online classes: A Study among University Students - Zahid Hussain; Muhammad Ishaq; Muhammad Imran; Muhammad Irfan Ahmed; Ghulam Yaseen; Maria Zafar (RADINKA JAYA UTAMA PUBLISHER, 2022)
Over the past few years, worries about the quality of online learning in higher education have increased. There has not been much research done on the quality of online education. It has been extensively researched how educators and administrators feel about online learning. In this qualitative study, we questioned students from different universities in Pakistan. The interview will be conducted through the WhatsApp video call; our respondents were thirty-five males and thirty-eight females. We interviewed seventy-three students. Materials on paper and online education data were gathered. They examined both the positive and negative aspects of students. They also learned what caused these occurrences. The interviews showed that students liked instructional interfaces that were flexible, inexpensive, based on electronic research, easy to find on the Internet, and well-designed. The students' bad experiences were caused by several things, such as slow teacher feedback, a lack of technical support, a lack of self-control and motivation, a feeling of isolation, repeated teaching methods, and poorly organized course material. The results can help teachers better comprehend how their students feel about online education.